Analysis of the Quality of Vermicompost from Mixed of Sawdust, Banana Stems, Manure, and Vegetable Waste - Shella Destia; Hilwa Walida; Saragih Hartati Yusida Siti; Mustamu Elizabeth Novilda; Harahap Syawal Fitra (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
Excessive and continuous use of inorganic fertilizers can pollute the environment. Therefore, to support sustainable agriculture, other alternatives are needed to meet the nutrients, namely the use of organic fertilizers, such as vermicompost fertilizer. This study used sawdust, banana weevil, cow dung, and vegetable waste as the feed and media for the cultivation of earthworms. This study aims to determine the content of N, P, K, C-org, C/N, and pH in the vermicompost fertilizer product Earthworm cultivation was carried out from December 2020 to March 2021 in Perlabian Village, Kampung Rakyat District, South Labuhanbatu Regency. Worm cultivation was carried out with two feeding treatments. The first treatment was given 1 kg of cow dung which had been diluted with 1 liter of water plus 250 grams of vegetable waste (K1) and the second treatment was given 2 kg of cow dung diluted in 1 liter of water and 500 grams of vegetable waste (K2). Feeding is conducted every 2 to 3 days for 1 month. The results of the next study were analyzed descriptively (comparing the results of the study with the standard compost of SNI-19-7030-2004). The test results showed that K1 vermicompost contained C-Org of 8.89%, N of 0.75%, P of 0.16%, K of 0.26%, C/N of 11.85, and pH of 6.5. The K2 vermicompost comprised C-Org of 10.92%, N of 0.86%, P of 0.16%, K of 0.23%, C/N of 12.69, and pH of 6.5. Based on the results of the analysis, the vermicompost produced in this study met the SNI-19-7030-2004 standard as compost and the K2 vermicompost contained higher organic and nitrogen content than the K1 vermicompost.